Framework for a System of Systems Design Oriented to Evolution - 赵青松 熊伟涛 王晓攀 杨克巍 (东华大学学报（英文版）, 2016)
A framework was proposed for designing a system of systems（SoS） that takes account of the system＇ s evolution over time.Given the design space of the SoS analysis,construct a multiepoch scenario design,SoS optimization,and robust designs.A hybrid model based on multi-agent and system dynamic models was used to analyze the evolution of an SoS and find robust designs.The framework can help decision makers generate a robust SoS structure based on the SoS＇ s capabilities over multiple epochs.